2020
DOI: 10.1177/1049909120915461
|View full text |Cite
|
Sign up to set email alerts
|

Generalist Palliative Care in the California Safety Net: A Structured Assessment to Design Interventions for a Range of Care Settings

Abstract: Background: To provide high quality care to all patients who have serious illness, health-care systems must develop effective generalist palliative care strategies. Objective: To identify palliative care quality gaps within a range of settings in the California safety net and to develop theory-based interventions to address them. Design: Structured assessment using the National Consensus Project for Quality Palliative Care Clinical Practice Guidelines and a Predisposing, Reinforcing, and Enabling Constructs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“… 26 In addition, sources emphasized the transparency of roles. 37 Anderson et al 29 found that EHRs were a barrier to communicating plans as they lacked the proper system- wide rollout to be useful and lead to some miscommunication between providers and finding patient history from other providers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 26 In addition, sources emphasized the transparency of roles. 37 Anderson et al 29 found that EHRs were a barrier to communicating plans as they lacked the proper system- wide rollout to be useful and lead to some miscommunication between providers and finding patient history from other providers.…”
Section: Resultsmentioning
confidence: 99%
“…32,46 Emphasis was placed on the importance of effectively and accurately identifying patients that needed, or were expected to need, comprehensive care. 29 Comprehensive care entailed using a multi-level lens and enrapturing multiple healthcare viewpoints, being part of a multidimensional practice could add in this practice 29 as well as triaging and calling on community resources if needed. 36 When the care plan was comprehensive and multidisciplinary, patients viewed their entirety of care from a team-based and holistic perspective.…”
Section: Simmons 50 ✔mentioning
confidence: 99%